Trends in functional programming : 13th International Symposium, TFP 2012, St. Andrews, UK, June 12-14, 2012, Revised Selected Papers - Pena, Ricardo; Loidl, Hans-Wolfgang (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed revised selected papers of the 13th International Symposium on Trends in Functional Programming, TFP 2012, held in St Andrews, Scotland, UK in June 2012. The 18 revised full papers included in this volume were carefully and selected from 49 submissions and are complemented with an invited paper. They cover various aspects of trends in functional programming.